RESPON PESERTA DIDIK PADA METODE PEMBELAJARAN YANG DIGUNAKAN GURU DALAM PEMBELAJARAN DARING - Nabilah Frederica Aristawati (BASA Journal of Language & Literature, 2022)
Various kinds of learning methods are used by educators in online learning so that students' responses are more varied. This study aims to find out how students respond to the learning methods used by teachers during online learning. The method used in this research is descriptive qualitative through a survey where the information is obtained from respondents via Google forms. The results showed that the majority of students stated that the online learning atmosphere tended to be passive and the teachers were less or not able to convey material as well as during offline learning. The learning methods that are widely used are discussions, exercises, and lectures using zoom meeting media. Most students stated that online learning was effective, but several others stated that online learning was sufficient, lacking, or even ineffective. It was calculated that 85% of the 78 respondents chose to carry out learning offline, because it was more fun and the material presented was well received. This shows that students' interest in online learning is still low, online learning makes their assignments more and more and not a few teachers enter the class only giving assignments without explaining any material. This indicates that the learning methods used by teachers are less acceptable to students, the various responses indicate that online learning has deficiencies in delivery in various circles.